The artistic phenomenon in the selected poetry of Bahnam Atallah - Alhadithy, Samer Ibrahim Jubair; Hajimaming @ Toklubok, Pabiyah; Mohamed, Ab Halim (Faculty of Languages, Al-Madinah International University, 2018)
This study is dedicated to tackle one of the major issues that preoccupied the mainstream of our contemporary critics namely the artistic phenomenon for the reason that it is for several poets a uniqueness. For Behnam Atallah in particular, whose poems were a field approached by critics and researchers due to its artistic aspects. This research aims at revealing how the poet employs a number of elements in his poetry, representing the language, image and rhythm. We have restricted the study to the poetry of Behnam Attalla and his poetical feats in a period from 1982 to 2012 in which his poems included relevant experiences in a historical point of view. The research statement exist in his qualitative poetical experience that is considered to be one of the most significant whether in Iraqi or Arabic poetry. As he does not publish his poem unless he examined its thorough process. Therefore, this research is aimed to handle this experience in his works in the context that analyses its chief elements, experience methods and nationality. The author will employ that method that he found to be the optimal for such type of studies with artistic features that is to be the descriptive- analytic method that deals with the text as an independent structure and self-sufficient that enabled the to grant the method a literary an aesthetic beauty focused on the linguistic composition esthetics, form. as well as it granted the rhythmic character to the poetic text. So it is hoped the researcher r comes up with some conclusion which include: that the Behnam Atallah,s poem characterized and excelled in his language poetic construction as his poem is based on the high standards in the poetry point of view in addition to linguistic stylistic phenomena, his poetic image stands on the material of the painting rather than on the article. The rhythm is also a compensation for the rhythm of the internal rather than the meter system and rhyme.